Perception regarding hypertension treatments and prevention of hypertension complications among individuals with hypertension - Dewi, Trisna Setya; Prabandari, Yayi Suryo; Ratrikaningtyas, Prima Dhewi (Universitas Gadjah Mada, 2022)
Purpose: This study aims to explore hypertension patients' perceptions about hypertension treatments and preventing hypertension complications. Method: This study was qualitative and phenomenological. Informants were selected using purposive sampling. The study was performed on 12 individuals with hypertension, three family members of an individual with hypertension, and one health worker. Data were collected using in-depth interviews and a semi-structured interview guide. This study's trustworthiness was achieved using triangulation data sources and member checking. Results: Informants in this study perceived that hypertension treatments consist of pharmacological and herbal treatments. Informants who stopped taking antihypertensive admitted that they did not feel the effectiveness of antihypertensive and felt more effective with herbal treatments. They were also afraid of the long-term side effects of drugs and thought that herbal treatments had no long-term side effects. The informants who felt the effectiveness of antihypertensive regularly continued the treatment and combined it with herbal treatment. The treatments carried out by the informant aim to prevent complications of hypertension; besides that, the informant also believes that a healthier lifestyle can prevent complications. Conclusion: The effectiveness of hypertension treatments that individuals feel can affect their' continuation of the treatments they did. The individuals who did not feel the benefits of treatment tend to take another treatment that is considered more effective. Their concern about hypertension complications is the reason for their adherence to both pharmacological and herbal treatment.